Peningkatan Hasil Belajar Kognitif Bahasa Indonesia Menggunakan Model CTL Siswa Kelas III SDN 4 Kotagede - Yuli Kartika Sari; C.Indah Nartani; Fathonah (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2021)
Based on the results of observations at SDN Kotagede4 it was found that the implementation of Indonesian language learning was not optimal in applying the learning model. This study aims to improve the cognitive learning outcomes of the third grade students of SDN Kotagede4 Indonesian language by using the CTL model. This research was conducted at SDN Kotagede4 with 29 students. The research design used was the Kemmis and MC Taggart model. Data collection techniques used are tests, observations, documentation. The data analysis used is quantitative and qualitative. The results showed that the steps of implementing the CTL model were able to improve the cognitive learning outcomes of the third grade Indonesian language at SDN Kotagede4. The increase is seen in the number of students who complete the KKM in each cycle. In the pre-action students who completed the KKM as many as 13 then the first cycle increased to 15. In the second cycle the number of students who completed the KKM increased again to 25. Thus, it can be concluded that the use of the CTL model succeeded in improving the cognitive learning outcomes of the third grade students of SDN Kotagede4.